Uric Acid Levels in Pregnant Women - Haribaik, Anastaysia Annisa; Bekti, Heri Setiyo; Posmaningsih, Dewa Ayu Agustini (Muhammadiyah Medical Journal, 2022)
Background: Preeclampsia in pregnant women can be detected by measuring uric acid levels in the blood. This can occur due to changes in the hemodynamic system and decreased glomerular filtration rate during pregnancy. Purposes: This study aims to determine the description of uric acid levels in pregnant women at Community Health Centers I, South Denpasar. Methods: This study uses a descriptive observational method from April to May 2022, with 31 respondents obtained by non-probability sampling technique. Uric acid levels were measured by the Point of Care Testing (POCT) method. Results: The results showed 23 pregnant women (74.2%) with normal uric acid levels and eight pregnant women (25.8%) with high uric acid levels. Conclusion: High uric acid levels are most suffered by pregnant women aged 30 years (16.1%), most commonly found in the third trimester of pregnancy (16.1%), most pregnant women with a body mass index (BMI) more and obesity (9.7%), and pregnant women with normal blood pressure (22.6%).